Should face masks be worn to contain the spread of COVID-19 in the postlockdown phase?. (19th September 2020) - Landi, Francesco; Marzetti, Emanuele; Sanguinetti, Maurizio; Ciciarello, Francesca; Tritto, Marcello; Benvenuto, Francesca; Bramato, Giulia; Brandi, Vincenzo; Carfì, Angelo; D'Angelo, Emanuela; Fusco, Domenico; Lo Monaco, Maria Rita; et al.
Abstract: Background: In East Asia, face masks are commonly worn to reduce viral spread. In Euope and North America, however, their use has been stigmatised for a long time, although this view has radically changed during the ongoing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. Notwithstanding this, it is still unclear whether face masks worn by COVID-19 carriers may indeed prevent viral transmission and environmental contamination. The objective of this study was to evaluate the effectiveness of surgical face masks in filtering SARS-CoV-2. Methods: Four male patients with COVID-19 were recruited for the study. Two patients wore a surgical mask for 5 h, while two others did not. The spread of the virus in the environment was evaluated through the approved Allplex 2019-nCoV assay. Results: In the room with the two patients without surgical masks, the swab performed on the headboard and sides of the beds was positive for SARS-CoV-2 contamination. In the other room, where two patients were wearing surgical masks, all of the swabs obtained after 5 h tested negative. Conclusions: The results of the current study add to the growing body of literature supporting the use of face masks as a measure to contain the spread of SARS-CoV-2 by retaining potentially contagious droplets that can infect other people and/or contaminate surfaces. Based on the current evidence, face masks should therefore be considered a useful and low-cost device in addition to social distancing and hand hygiene during the postlockdown phase.